Маркетингове управління підприємств залізничного транспорту: шляхи розкриття потенціалу - Чорнописька, Н. В.; Стасюк, К. З.; Chornopyska, N. V.; Stasiuk, K. Z. (Видавництво Львівської політехніки, 2022)
Здійснено емпіричні дослідження маркетингового управління підприємств залізничного транспорту (перевізників). Отримано цілісну картину рівня маркетингового управління потенціалом підприємств залізничного транспорту. Досліджено їхні маркетингову політику, інноваційну політику, інвестиційний клімат, інформаційне забезпечення. Сформовано портрет підприємств, що репрезентують ринок залізничних вантажних перевезень України.

Purpose: to form a general understanding of marketing management level in regard to railway transport enterprises (carriers). Methodology. Empirical methods were used to achieve the research purpose, namely, a survey of enterprise managers representing the rail freight transportation market. Data collection tool used – Google Form questionnaire including 6 thematic question blocks (33 questions in total). The questionnaire incorporated questions of a different nature, namely: open, closed, alternative, ranking, attitude scale, rating scale, importance scale. Communication between the respondent and the researchers was carried out online using e-mail (30 %), Facebook (50 %), LinkedIn (20 %). Findings. The research conducted proved railway freight transport market enterprises are focused on the cargo, and not on the client; despite accumulated problems characterizing the industry, the rail freight transport market of Ukraine remains attractive for investment; modern realities demand all the spheres of economy to demonstrate considerable level of flexibility – information technology implementation proved to be vital now; innovations play a significant role in the industry development and have a significant impact on the efficiency and image of both the industry and the country. Practical implications. The results this study provides are of particular interest to the railway transport market enterprise managers seeking to improve their marketing strategy compliance with modern conditions and to strengthen their competitive position on the market. In addition, the results provide stakeholders with ability of improving the marketing communication tools used to build and maintain B2B interactions in the rail freight market. Value. The study presents marketing research results along in-depth analysis indicating existence of a rationale for increased attention to marketing management of enterprises, implementation of effective marketing and logistics mechanisms, as well as increased attention to digitalization in the conditions of railway freight transportion market liberalization.
Marketing management applied to railway transport enterprises: ways of disclosing the potential
Keywords: підприємства залізничного транспорту; перевізники; маркетингове управління; ринок залізничних вантажних перевезень; потенціал; railway transport enterprises; carriers; marketing management; railway freight transportation market; potential; 330.341.1; 658.8